Role and Place of Antibacterial Therapy in Prophylaxis of Disturbances in Reproductive Function of Women - E. V. Utkin; N. M. Podonina; N. I. Kordubailova (Антибиотики и Химиотерапия)
One-stage retrospective analysis of 350 primary medical documents of the female patients treated under hospital conditions for salpingo-oophoritis in 2010-2011 was performed. The results were compared with those of the investigation of the present etiological pattern of pelvic inflammatory diseases (PID) by the data of the microbiological examination of 117 patients with PID and susceptibility of the isolates to the antibacterials. The frequency and efficiency of the use of antibacterials alone or in combinations were analysed in the treatment of various clinical forms of PID. The ovarian reserve was estimated in 87 patients after recovery from salpingo-oophoritis. 52 of them had an episode of the chronic process exacerbation and 35 had the first episode of acute PID. The ovarian reserve was estimated by determination of the anti-Mullerian hormone (AMH), basal FSH level, ovarian volume and antral follicle count. A statistically significant decrease of the ovarian reserve in the patients with chronic salpingo-oophoritis confirmed the necessity of rational treatment of the acute inflammatory process.